Gestational age estimation using transcerebellar diameter with grading of fetal cerebellar growth - Anirban Das Gupta; Arindom Banerjee; N Rammurthy; P Revati; Josna Jose; P Karak; Anil Kumar (Wolters Kluwer Medknow Publications, 2012)
Background: The transverse cerebellar diameter (TCD) serves as a reliable predictor of gestational age (GA) of the fetus and is a standard against which aberrations in other fetal parameters can be compared, especially when the GA cannot be determined by the date of the last menstrual period or an early pregnancy scan. Aim: The aim of this study was to derive a regression equation and evaluate the relationship between transverse cerebellar diameter and gestational age, which will be helpful in assessing the fetal gestational age and also to evaluate the grades of cerebellum and to see its growth. Materials & methods: The prospective study was carried out in 292 pregnant women between 14-40 weeks of pregnancy attending the Konaseema Institute of Medical Sciences & Research Foundation, Amalapuram for routine ultrasound examination. Transverse cerebellar diameter was measured and cerebellum was graded using ultrasonography. Results: Fetal cerebella were found to be in 29%, 10% and 61% cases as grade I, II and III respectively. The grade changed from I to III progressively with advancing gestation. The median GA and TCD were 20 wks and 22 μm for grade I, 32 wks and 30 mm for grade II and 36 wks and 38 mm for grade III. Conclusion: Regression analysis indicated a strong relationship between TCD and gestational age indicating TCD is a good marker for estimation of gestational age.